Simeprevir for the treatment of hepatitis C and HIV/hepatitis C co-infection. Issue 6 (November 2014) - Flanagan, Stuart; Crawford-Jones, Andrew; Orkin, Chloe
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV) is a major cause of chronic hepatitis in 170 million people worldwide and can progress to fibrosis, cirrhosis, liver failure and hepatocellular carcinoma, a disease process accelerated in HIV co-infection. Approximately 25% of HIV infected people are co-infected with HCV (worldwide prevalence 4–5 million) and up to 16.7% of deaths in this population are attributable to HCV co-infection. Previous treatment options for HCV were limited to pegylated interferon and ribavirin (PEG-IFN/RBV), a combination that demonstrated lower successful cure rates in genotype 1 HCV mono-infection and HIV/HCV co-infection, and is also associated with a considerable adverse side-effect profile. The development of directly acting antivirals (DAAs) offers the first class of drug to achieve good viral suppression in previously hard-to-treat patient groups. We review the benefits, tolerability and drug interactions with concomitant drugs of the DAA simeprevir for patients who have HCV mono-infection and hep C/HIV co-infection.